Fast hologram reconstruction algorithm in digital in-line holography using Toeplitz matrix based deconvolution. (December 2022) - Ghosh, Anik; Kulkarni, Rishikesh; Shin, Seunghyup; Mondal, Pranab Kumar
Highlights: Toeplitz matrix-based deconvolution technique is proposed for hologram reconstruction. A procedure to avoid the aliasing effect in the reconstructed images is discussed. The reconstruction technique is applicable in digital in-line holography. High computational efficiency is offered by proposed method compared to FFT. Abstract: A new hologram reconstruction algorithm is proposed for digital in-line holography configuration using the Toeplitz matrix based deconvolution. The variable separable property of the convolution kernel associated with hologram recording and reconstruction process allows the matrix formulation of deconvolution. A procedure to avoid the aliasing effect in the reconstructed images is discussed. The proposed method is found to provide improved computational efficiency in comparison to the conventional FFT based deconvolution approach without compromising the reconstruction quality. Simulation and experimental results substantiate the practical applicability of the proposed method.